A ceramic surface modified anti-adhesion anti-clogging ventricular shunt and a preparation method thereof
Patent Information
- Application Number
- CN202611416913.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明旨在解决现有脑室腹腔分流管易蛋白吸附、腹腔网膜包裹、端口受压变形、长期堵管翻修率高,以及传统制备工艺无环保配套、不分管径规格、缺少长期老化检测标准的问题
1)复合陶瓷涂层通过二氧化钛与羟基磷灰石的协同作用,集成了三重防护机制,能够同步改善蛋白沉积堵管、网膜组织包裹堵管、端口挤压形变堵管三类临床常见问题,突破了传统单一功能涂层防护的局限性。特别是,特定配比的复合涂层在模拟脑脊液的体外流体剪切条件下,展现出远超单一组分的动态自清洁能力,且该能力在长期老化后依然保持稳定。涂层不负载药物,无药物耗竭问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] Hydrocephalus is a common neurosurgical disease, and ventriculoperitoneal shunt surgery is currently the main treatment for hydrocephalus. However, long-term blockage of the shunt tube is a core pain point that needs to be addressed in clinical practice. The incidence of shunt tube blockage can reach 30%-40% 2-5 years after surgery, requiring patients to undergo multiple revision surgeries, increasing patient trauma and the financial burden of medical care. Background Technology
[0002] Hydrocephalus is a common neurosurgical disease, and ventriculoperitoneal shunt surgery is currently the main treatment for hydrocephalus. However, long-term blockage of the shunt tube is a core pain point that needs to be addressed in clinical practice. The incidence of shunt tube blockage can reach 30%-40% 2-5 years after surgery, requiring patients to undergo multiple revision surgeries, increasing patient trauma and the financial burden of medical care.
[0003] There are three major problems with existing silicone and polyurethane polymer shunt tubes: (1) The polymer has a high surface energy, which makes it easy to adsorb fibrin and inflammatory cells in the cerebrospinal fluid, and quickly form a biofilm, causing the ventricular end drainage hole to gradually close, and the choroid plexus tissue to grow inward, further aggravating the blockage; (2) The outer wall of the shunt tube has a high friction coefficient, and after implantation in the abdominal cavity, it is in continuous contact with the greater omentum and abdominal wall soft tissue, which can easily induce connective tissue adhesion and pseudocyst encapsulation, ultimately leading to the failure of abdominal end drainage; (3) The polymer material has excellent flexibility but insufficient surface hardness. When the ventricular end is compressed by brain tissue, the subcutaneous tube is squeezed by fascia, and the abdominal end is squeezed by abdominal pressure, the port and side hole are prone to collapse and deformation, causing mechanical blockage.
[0004] To address the issue of shunt tube blockage, existing technologies have focused on material modification, surface coating modification, and device structure optimization. Patent CN110694118A discloses a silicone tube body for an antibacterial and anticoagulant ventriculoperitoneal shunt, in which antibacterial and anticoagulant agents are co-added into the silicone matrix, achieving antibacterial and anticoagulant effects through the material itself. However, this approach lacks a functional surface coating, limiting its ability to inhibit cerebrospinal fluid protein adsorption and failing to provide targeted reinforcement of the tube wall's mechanical properties. Patent CN117736618A discloses a novel antibacterial and antifouling coating material using a phosphocholine-based hydrophilic copolymer coating, which provides short-term lubrication and moisture retention on the catheter surface and passively inhibits protein and polysaccharide adsorption. However, this coating is a passive antifouling system and lacks dynamic self-cleaning capabilities. The patent does not address coating durability and anti-aging design for long-term cerebrospinal fluid immersion environments and only modifies the catheter surface, failing to improve the hardness of the catheter wall and thus unable to resist external extrusion deformation. Patent CN103800991A discloses a ventriculoperitoneal shunt device for preventing blockage. It uses a Y-shaped tubing with a shunt pump, a programmable switch and an electronic control system. It relies on electromechanical control to switch pathways and actively drive the flow of cerebrospinal fluid, thus mitigating the risk of blockage from the structural level of the device. However, this solution does not address the root causes of blockage such as protein adsorption and tissue adhesion from the perspective of modifying the surface of the catheter material. The device has a complex structure, which limits its clinical implantation and promotion.
[0005] Existing technologies, including the aforementioned patents, struggle to simultaneously address the three requirements of inhibiting protein deposition, reducing tissue adhesion, and resisting external extrusion deformation. They also cannot simultaneously overcome the three types of clinical problems: biofilm blockage, tissue encapsulation blockage, and mechanical deformation blockage, resulting in significant limitations in clinical application. Furthermore, existing ceramic surface modification processes are mostly generalized systems lacking long-term coating performance evaluation standards. Directly applying these modification processes to pipelines of different diameters easily leads to defects such as uneven coating thickness and poor coating adhesion, hindering large-scale industrial application.
[0006] Therefore, it is necessary to develop a multifunctional surface-modified ventriculoperitoneal shunt tube that can be adapted to different tube diameters and simultaneously inhibit protein deposition, reduce tissue adhesion, and resist external force compression deformation. Summary of the Invention
[0007] This invention aims to address the problems of existing ventriculoperitoneal shunts, such as easy protein adsorption, omental wrapping, port deformation under pressure, high long-term clogging and repair rates, and the lack of environmental protection support, indiscriminate use of different pipe diameters, and lack of long-term aging testing standards. To this end, this invention provides a method for preparing a ceramic-modified, anti-sticking, and anti-clogging ventriculoperitoneal shunt. This invention improves three main types of clogging failure problems through three synergistic core mechanisms: low protein adsorption of the bioceramic coating, dynamic self-cleaning under simulated physiological fluid conditions, and enhanced local support hardness around the pipe wall and drainage holes. Simultaneously, for different pipe diameters, differentiated cooling rates and holding times are set to establish a gradient low-temperature curing system, along with a closed-loop treatment process for harmless waste liquid and exhaust gas, and accelerated aging testing quality control standards for the coating. These improvements enhance the shunt's patency-related performance, potentially reducing the risk of clogging, meeting the requirements for large-scale green and safe production of medical devices, and effectively extending the stable service life of the shunt.
[0008] To achieve the above objectives, the present invention provides a ceramic-modified anti-sticking and anti-clogging ventriculoperitoneal shunt, comprising a shunt substrate made of medical flexible polymer.
[0009] Furthermore, the medical flexible polymer substrate is made of polyurethane or medical silicone, both of which have excellent biocompatibility and are suitable for long-term intracranial and peritoneal implantation environments.
[0010] Furthermore, the shunt tube is divided into a ventricular segment, a valve connection segment, and a peritoneal segment; the entire inner wall, outer wall, drainage side hole, and end port surface of the ventricular and peritoneal segments of the shunt tube are covered with a dense titanium dioxide-hydroxyapatite composite bioceramic coating, with no missed coatings and no exposed substrate areas.
[0011] Furthermore, the mass ratio of titanium dioxide to hydroxyapatite is 1:(0.8-1.2), and the resulting composite ceramic combines the advantages of high inertness and high hardness of titanium dioxide with the excellent biocompatibility of hydroxyapatite. When the proportion of titanium dioxide is higher than 1, the biocompatibility of the coating decreases; when the proportion of hydroxyapatite exceeds 1.2, the overall hardness of the coating decreases and the end-capacity for extrusion deformation is significantly reduced. 1:(0.8-1.2) is the optimal ratio range for achieving low protein adsorption, high hardness, and excellent biocompatibility in vivo in this invention.
[0012] The composite bioceramic coating described in this invention is not a simple physical mixture of titanium dioxide and hydroxyapatite; rather, the two materials produce a synergistic effect under specific proportions. Titanium dioxide provides mechanical support and chemical inertness to the coating; hydroxyapatite improves the coating's biocompatibility and regulates its surface energy and microstructure, promoting the desorption of adsorbed proteins under the shear force of cerebrospinal fluid, thus achieving the dynamic self-cleaning described in this application. The "dynamic self-cleaning" described in this application refers to the desorption of physically adsorbed proteins and cell debris on the coating surface under the shear force of fluid under simulated continuous cerebrospinal fluid flow and micro-displacement of the shunt tube caused by physiological activities in vivo, achieving surface renewal. It is expected that similar effects can be achieved under conditions of cerebrospinal fluid flow and micro-displacement of the tubing in vivo. The composite ceramic coating retains the overall flexibility of the polymer substrate while increasing local hardness to resist port compression and collapse; the coating possesses good biocompatibility and resistance to cerebrospinal fluid corrosion, meeting the requirements for long-term implantation and use of the shunt tube.
[0013] Furthermore, the walls, drainage side holes, and ends of the ventricular and peritoneal segments are key areas for modification with a composite bioceramic coating, aiming to address two common clinical problems: protein blockage at the ventricular end and omental wrapping at the peritoneal end.
[0014] Furthermore, the composite bioceramic coating has a thickness of 500-800 nm, is dense and non-porous, and contains no easily detached particles. The surface roughness of the coating is controlled within the range of 0.03-0.05 μm, forming an ultra-low friction smooth interface.
[0015] Furthermore, the Vickers hardness of the composite bioceramic coating is 4-4.5 times that of the medical flexible polymer substrate, which improves the resistance to compression and collapse deformation of the diversion tube drainage port and the small side hole, and prevents the lumen from being compressed and narrowed and blocked.
[0016] This invention also provides a method for preparing the above-mentioned ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt, comprising the following steps: 1) Substrate pretreatment: The molded polymer manifold is ultrasonically degreased and cleaned sequentially with anhydrous ethanol and deionized water to remove oil stains and demolding impurities from the pipe wall. Then, oxygen plasma is used to activate all the inner and outer surfaces of the pipe. The oxygen plasma activation time is 5-15 minutes, which effectively improves the interfacial bonding strength between the ceramic coating and the medical flexible polymer substrate. The manifold is dried to remove water, so as to avoid residual moisture affecting the uniformity of subsequent ceramic sol film formation. The waste liquid generated during cleaning is collected, neutralized and filtered, and then disposed of harmlessly. The organic exhaust gas generated during activation is treated by a catalytic purification device and discharged in compliance with standards.
[0017] 2) Ceramic Precursor Deposition: A sol-gel negative pressure wetting method is employed. Air is removed from the inner cavity and side holes of the pipeline using negative pressure, allowing the ceramic sol to completely wet the entire inner and outer walls of the manifold, the drainage side holes, and the surfaces of both ends, uniformly depositing a ceramic precursor film. After wetting, residual sol waste liquid in the equipment is collected in a sealed environment, filtered, purified, and recycled to reduce raw material loss. The negative pressure wetting process is completed in a sealed, clean chamber, isolating dust and impurities throughout to prevent defects on the coating surface. This deposition step can be replaced by vacuum magnetron sputtering (suitable for medical silicone substrate tubing), with the chamber evacuated to 1.0 × 10⁻⁶. -4 After a high vacuum of Pa, a trace amount of oxygen is introduced, and simultaneous co-sputtering with a pure titanium target and a hydroxyapatite target is used. The overall power is 200W. Titanium dioxide and hydroxyapatite components are deposited simultaneously, and their mass ratio is controlled to be 1:(0.8-1.2). During the sputtering process, the plasma is guided into the inner wall of the tube by an auxiliary anode bias voltage inside the tube. The auxiliary anode bias voltage inside the tube is controlled between -150V and -80V. Both processes can form a uniform and dense composite ceramic coating on the entire surface of the shunt tube.
[0018] 3) Low-temperature gradient curing and crystallization: Two independent low-temperature gradient temperature rise crystallization programs are set up to adapt to different pipe diameter specifications and avoid high-temperature cracking and aging of thin pipes; the adult standard pipe program is 50℃ for 30min, 65℃ for 40min, and 80℃ for 20min; the children's thin pipe program is 50℃ for 20min, 62℃ for 30min, and 75℃ for 15min; after curing, a natural and slow cooling method is used to release the internal thermal stress of the coating.
[0019] 4) Surface passivation and polishing: After curing and crystallization, the pipeline undergoes high-precision polishing over its entire surface using diamond micropowder. W0.25-W0.5 diamond micropowder is selected for polishing; the polishing speed is 150-250 rpm, and the polishing time is 8-15 minutes. Afterwards, the pipeline is immersed in a medical passivation solution for thorough passivation treatment, sealing micropores, protrusions, and other microscopic defects on the coating surface, thereby improving the coating's wear resistance and resistance to bodily fluid corrosion. The medical passivation solution is a commonly used dilute nitric acid-based passivation solution in the field of medical device ceramic coatings, which can passivate and seal microscopic defects on the ceramic coating surface; the immersion time is controlled at 8-12 minutes. After surface passivation and polishing, the pipeline is repeatedly rinsed with sterile deionized water and dried for later use.
[0020] 5) Testing and Packaging: The finished product undergoes full performance testing in a Class 100,000 cleanroom. The basic testing items include four core indicators: coating adhesion, Vickers hardness, in vitro protein adsorption, and cytotoxicity. Accelerated aging and wear simulation tests of the coating are also conducted. After all indicators pass the tests, the product is sterilely vacuum-sealed and packaged for storage.
[0021] The beneficial effects of the technical solution provided by this invention are as follows: 1) The composite ceramic coating integrates a triple protection mechanism through the synergistic effect of titanium dioxide and hydroxyapatite, simultaneously improving three common clinical problems: protein deposition clogging, omental tissue encapsulation clogging, and port compression deformation clogging, overcoming the limitations of traditional single-function coatings. In particular, the composite coating with a specific ratio exhibits a dynamic self-cleaning ability far exceeding that of a single component under simulated in vitro fluid shear conditions of cerebrospinal fluid, and this ability remains stable even after long-term aging. The coating does not carry drugs, eliminating the problem of drug depletion.
[0022] 2) Differentiated low-temperature gradient curing processes are designed for adult and pediatric tubing to prevent heat cracking of thin-diameter tubing and aging and hardening of the polymer substrate; the coating of thin-diameter tubing for children does not crack or peel off under this low-temperature process, and the hardness, protein desorption, and adhesion indicators meet the requirements for medical device implantation; the tubing substrate retains its original flexibility, which facilitates minimally invasive clinical implantation.
[0023] 3) The coating of this invention has been verified by accelerated aging and wear tests, showing that it has a strong and stable structure, excellent wear resistance and anti-aging properties, effectively assesses and ensures the safety of long-term implantation, and improves implantation safety performance.
[0024] 4) The entire process adopts a mild and low-temperature preparation process, and plasma activation improves the coating bonding strength. The yield rate of finished products is high, the process is stable and controllable, and it is suitable for large-scale industrial production. The coating has good stability and is expected to improve the problem of blockage in the diversion pipe. Attached Figure Description
[0025] Figure 1 A schematic diagram of a ceramic-surface-modified ventriculoperitoneal shunt.
[0026] Figure 2 A schematic diagram of the cross-section of the ceramic coating on the ventriculoperitoneal shunt.
[0027] Figure 3 Schematic diagram of low protein adsorption in ceramic-modified ventriculoperitoneal shunt.
[0028] Figure 4 A schematic diagram of the dynamic self-cleaning mechanism of ceramic-modified ventriculoperitoneal shunt.
[0029] Figure 5 A schematic diagram illustrating the anti-extrusion deformation mechanism of ceramic-modified ventriculoperitoneal shunt tubes;
[0030] Figure labels: 1. Ventricular segment; 2. Valve connection segment; 3. Abdominal segment; 4. Drainage side hole; 5. Medical flexible polymer substrate; 6. Composite bioceramic coating; Detailed Implementation
[0031] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0032] Example 1 This embodiment provides a ceramic-modified, anti-sticking, and anti-clogging ventriculoperitoneal shunt. The shunt's medical flexible polymer substrate 5 is integrally molded using medical implant-grade polyurethane, conforming to adult standard specifications. The medical flexible polymer substrate 5 has an inner diameter of 3.0 mm and an outer diameter of 4.2 mm. The composite bioceramic coating 6 on the shunt surface is composed of titanium dioxide and hydroxyapatite in a 1:1 mass ratio. The coating thickness is 650 nm, the surface roughness is 0.04 μm, and the Vickers hardness of the coating is 4.25 times that of the corresponding medical flexible polymer substrate 5.
[0033] The preparation method of the ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt described in this embodiment includes the following steps: (1) Substrate pretreatment: The ventriculoperitoneal shunt tube after molding was ultrasonically cleaned with anhydrous ethanol for 15 min to remove surface oil, impurities and processing residues. Then it was thoroughly rinsed with deionized water and dried for later use. The dried shunt tube was activated by oxygen plasma for 10 min, with the oxygen flow rate controlled at 50 mL / min and the plasma power at 100 W to activate the surface of the medical flexible polymer substrate 5 and improve the coating bonding performance.
[0034] (2) Ceramic precursor deposition: The sol-gel negative pressure wetting method is used to deposit a coating on the manifold. The coating is maintained at a vacuum of -0.08MPa for 5 minutes to ensure that the composite ceramic sol fully and uniformly covers the entire inner wall, outer wall, drainage side hole 4 and the surface of both ends of the manifold. After deposition, the residual sol is sealed, recycled, purified and reused to reduce raw material loss.
[0035] (3) Low temperature gradient curing and crystallization: a segmented gradient heating curing process is adopted, with a constant heating rate of 1℃ / min. The specific heating program is: 50℃ for 30min, 65℃ for 40min, and 80℃ for 20min. After curing and crystallization, the coating is slowly cooled to room temperature at a cooling rate of ≤0.5℃ / min to effectively release the internal thermal stress of the coating and avoid cracking and peeling of the coating.
[0036] (4) Surface passivation and polishing: W0.5 diamond micro powder is used to polish the entire surface area of the shunt tube at a polishing speed of 200 rpm and a polishing time of 10 min to remove micro-protrusions and defects on the coating surface; then the polished shunt tube is immersed in medical passivation solution for 10 min to complete the surface passivation modification, and after being taken out, it is repeatedly rinsed with sterile pure water and dried for later use.
[0037] (5) Aseptic packaging test: In a Class 100,000 clean production workshop, the modified shunt tube is tested for various performance indicators. After passing the test, it is sterile vacuum sealed and packaged to obtain the finished ceramic surface modified anti-stick and anti-clogging ventriculoperitoneal shunt tube.
[0038] Example 2 This embodiment provides a ceramic surface modified anti-sticking and anti-clogging ventriculoperitoneal shunt tube, which differs from Embodiment 1 only in that: the mass ratio of titanium dioxide to hydroxyapatite in the composite bioceramic coating 6 is 1:1.2, the coating thickness is 800nm, the coating surface roughness is 0.05μm, and the Vickers hardness of the coating is 4.5 times that of the medical flexible polymer substrate 5.
[0039] The material, specifications, and preparation method of the medical flexible polymer substrate 5 in this embodiment are completely consistent with those in Example 1. The above parameters are adjusted by adjusting the ratio of composite ceramic sol raw materials and the negative pressure deposition time.
[0040] Example 3 This embodiment provides a ceramic surface modified anti-sticking and anti-clogging ventriculoperitoneal shunt tube, which differs from Embodiment 1 only in that: the mass ratio of titanium dioxide to hydroxyapatite in the composite bioceramic coating 6 is 1:0.8, the coating thickness is 500nm, the coating surface roughness is 0.03μm, and the Vickers hardness of the coating is 4.0 times that of the medical flexible polymer substrate 5.
[0041] The material, specifications, and preparation method of the medical flexible polymer substrate 5 in this embodiment are completely consistent with those in Example 1, as are the other process parameters and operating steps.
[0042] Example 4 This embodiment provides a ceramic surface modified anti-sticking and anti-clogging ventriculoperitoneal shunt tube, which differs from Embodiment 1 only in that: the mass ratio of titanium dioxide to hydroxyapatite in the composite bioceramic coating 6 is 1:1.2, the coating thickness is 500nm, the coating surface roughness is 0.04μm, and the Vickers hardness of the coating is 4.25 times that of the medical flexible polymer substrate 5.
[0043] The material, specifications, and preparation method of the medical flexible polymer substrate 5 in this embodiment are completely consistent with those in Example 1, as are the other process parameters and operating steps.
[0044] Example 5 This embodiment provides a ceramic-modified, anti-adhesive, and anti-clogging ventriculoperitoneal shunt. The shunt's medical flexible polymer substrate 5 is integrally molded from medical implantable silicone, conforming to adult standard specifications. The medical flexible polymer substrate 5 has an inner diameter of 3.0 mm and an outer diameter of 4.2 mm. The composite bioceramic coating 6 on the shunt surface is composed of titanium dioxide and hydroxyapatite in a 1:1 mass ratio. The coating thickness is 650 nm, the surface roughness is 0.04 μm, and the Vickers hardness of the coating is 4.30 times that of the silicone of the medical flexible polymer substrate 5.
[0045] The preparation method of the ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt described in this embodiment includes the following steps: (1) Substrate pretreatment: The ventriculoperitoneal shunt tube after molding was ultrasonically cleaned with anhydrous ethanol for 15 min to remove surface oil, impurities and processing residues. Then it was thoroughly rinsed with deionized water and dried for later use. The dried shunt tube was activated by oxygen plasma for 12 min, with oxygen flow rate controlled at 40 mL / min and plasma power at 80 W to activate the surface of the medical flexible polymer substrate 5 and improve the coating bonding performance.
[0046] 2) Ceramic precursor deposition: The shunt tube was coated using vacuum magnetron sputtering, with the cavity evacuated to 1.0 × 10⁻⁶ mm. -4 After a high vacuum of Pa, a trace amount of oxygen is introduced, and a dual-target co-sputtering process using high-purity titanium and hydroxyapatite is employed with a total power of 200W. Titanium dioxide and hydroxyapatite components are deposited simultaneously, with the mass ratio of the two controlled at 1:1. During the sputtering process, an auxiliary anode bias is used inside the tube to guide the plasma into the inner wall of the tube cavity. The auxiliary anode bias is controlled at -100V, so that a dense titanium dioxide-hydroxyapatite composite bioceramic coating 6 is formed simultaneously on the inner wall, outer wall, drainage side hole 4, and both ends of the shunt tube, with a total deposition thickness of 650nm.
[0047] (3) Low-temperature gradient curing and crystallization: Since medical silicone polymers have weaker heat resistance than polyurethane, even for adult standard specification pipelines, a lower temperature gradient curing procedure is still selected to avoid the silicone substrate from aging and hardening due to heat. The heating rate is kept constant at 0.8℃ / min, and the specific heating procedure is: 50℃ for 20min, 62℃ for 30min, and 75℃ for 15min. After curing and crystallization, the substrate is slowly cooled to room temperature at a cooling rate of ≤0.5℃ / min to effectively release the internal thermal stress of the coating.
[0048] (4) Surface passivation and polishing: W0.5 diamond micro powder is used to polish the entire surface area of the shunt tube at a polishing speed of 200 rpm and a polishing time of 10 min. Then, the polished shunt tube is immersed in medical passivation solution for 10 min, and after being taken out, it is repeatedly rinsed with sterile pure water and dried for later use.
[0049] (5) Aseptic packaging test: In a Class 100,000 clean production workshop, the modified shunt tube is tested for various performance indicators. After passing the test, it is sterile vacuum sealed and packaged to obtain the finished ceramic surface modified anti-stick and anti-clogging ventriculoperitoneal shunt tube.
[0050] Example 6 This embodiment provides a ceramic-modified, anti-sticking, and anti-clogging ventriculoperitoneal shunt. The shunt's medical flexible polymer substrate 5 is integrally molded using medical implant-grade polyurethane, and is designed for pediatric use with a small diameter. The medical flexible polymer substrate 5 has an inner diameter of 1.5 mm and an outer diameter of 2.4 mm. The composite bioceramic coating 6 on the shunt surface is composed of titanium dioxide and hydroxyapatite in a 1:1 mass ratio, with a coating thickness of 600 nm and a surface roughness of 0.04 μm. Testing using a nanoindenter shows that the Vickers hardness of the coating is 4.20 times that of the corresponding medical flexible polymer substrate 5.
[0051] The preparation method of the ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt described in this embodiment includes the following steps: 1) Substrate pretreatment: The molded pediatric ventriculoperitoneal shunt tube was ultrasonically cleaned with anhydrous ethanol for 12 minutes to remove surface oil, impurities and processing residues. Then it was thoroughly rinsed with deionized water and dried for later use. The dried shunt tube was then subjected to oxygen plasma activation treatment for 8 minutes, with the oxygen flow rate controlled at 45 mL / min and the plasma power at 90 W, to activate the surface of the medical flexible polymer substrate 5 and improve the coating adhesion performance.
[0052] 2) Ceramic precursor deposition: The sol-gel negative pressure wetting method is used to deposit a coating on the manifold. The coating is maintained at a vacuum of -0.08MPa for 6 minutes to ensure that the composite ceramic sol fully and uniformly covers the entire inner wall, outer wall, drainage side hole 4 and the surface of both ends of the manifold. After deposition, the residual sol is sealed, recovered, purified and recycled to reduce raw material loss.
[0053] 3) Low-temperature gradient curing and crystallization: A segmented gradient temperature curing process is adopted for children's small-diameter pipes. The heating rate is constant at 1℃ / min. The specific heating program is as follows: 50℃ for 20min, 62℃ for 30min, and 75℃ for 15min. After curing and crystallization, the pipes are slowly cooled to room temperature at a cooling rate of ≤0.5℃ / min to effectively release the internal thermal stress of the coating and prevent the coating of small-diameter pipes from cracking and peeling off.
[0054] 4) Surface passivation and polishing: W0.25 diamond micro powder is used to polish the entire surface area of the shunt tube at a polishing speed of 180 rpm for 9 minutes to remove micro-protrusions and defects on the coating surface. Then, the polished shunt tube is immersed in medical passivation solution for 9 minutes to complete the surface passivation modification. After removal, it is repeatedly rinsed with sterile pure water and dried for later use.
[0055] 5) Aseptic Packaging Testing: In a Class 100,000 clean production workshop, the modified pediatric shunt tubes are tested for various performance indicators, including coating adhesion, Vickers hardness, in vitro protein adsorption, and cytotoxicity. Simultaneously, simulated cerebrospinal fluid immersion + 1 million cycles of cyclic bending accelerated aging and wear test are carried out. After all indicators pass the test, aseptic vacuum sealing is performed to obtain the finished pediatric ceramic surface modified anti-stick and anti-clogging ventriculoperitoneal shunt tube.
[0056] Example 7 This embodiment provides a ceramic-modified, anti-adhesive, and anti-clogging ventriculoperitoneal shunt tube, designed for pediatric use with a small diameter. The medical flexible polymer substrate 5 has an inner diameter of 1.5 mm and an outer diameter of 2.4 mm. The medical flexible polymer substrate 5 is made of medical implant-grade polyurethane. The composite bioceramic coating 6 has a titanium dioxide to hydroxyapatite mass ratio of 1:1.2, a coating thickness of 750 nm, and a coating surface roughness of 0.05 μm. The Vickers hardness of the coating is 4.40 times that of the medical flexible polymer substrate 5, as tested using a nanoindenter.
[0057] The specifications, pretreatment, deposition process, low-temperature gradient curing procedure for pediatric tubing, passivation and polishing, and testing and packaging steps of the medical flexible polymer substrate 5 in this embodiment are completely consistent with those in Example 6. The above coating parameters are achieved by adjusting the ratio of ceramic sol raw materials and the negative pressure wetting time.
[0058] Example 8 This embodiment provides a ceramic-modified, anti-adhesive, and anti-clogging ventriculoperitoneal shunt. The shunt substrate is integrally molded from medical implantable silicone, with a pediatric-sized, thin-diameter design. The medical flexible polymer substrate 5 has an inner diameter of 1.5 mm and an outer diameter of 2.4 mm. The composite bioceramic coating 6 has a titanium dioxide to hydroxyapatite mass ratio of 1:0.8, a coating thickness of 520 nm, and a surface roughness of 0.03 μm. Testing using a nanoindenter shows that the Vickers hardness of the coating is 4.10 times that of the medical flexible polymer substrate 5 silicone.
[0059] The preparation method of the ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt described in this embodiment includes the following steps: 1) Substrate pretreatment: The molded children's silicone shunt tube was ultrasonically cleaned with anhydrous ethanol for 12 min, rinsed with deionized water, and dried; oxygen plasma activation time was 10 min, oxygen flow rate was 35 mL / min, and plasma power was 75 W.
[0060] 2) Ceramic precursor deposition: Vacuum magnetron sputtering, chamber evacuated to 1.0 × 10⁻⁶ m³ / s. -4 High vacuum of Pa was applied, and a trace amount of oxygen was introduced. Pure titanium target and hydroxyapatite dual target co-sputtering was performed with a total power of 200W, and the TiO2:HA mass ratio was controlled to be 1:0.8. The auxiliary anode bias voltage inside the tube was -120V to guide the plasma into the inner wall of the small tube cavity, the drainage side hole 4, and the end, and a dense composite ceramic coating of 520nm was deposited.
[0061] 3) Low-temperature gradient curing and crystallization: Gradient program for children's thin-diameter silicone tubing, heating rate 0.8℃ / min; 50℃ for 20min, 62℃ for 30min, 75℃ for 15min; after curing, slowly cool at a rate of ≤0.5℃ / min to release thermal stress.
[0062] 4) Surface passivation and polishing: W0.25 diamond micro powder, 180 rpm, polishing for 9 min; soak in medical passivation solution for 9 min, rinse with sterile pure water and dry.
[0063] 5) Aseptic packaging test: In a Class 100,000 cleanroom, the coating adhesion, Vickers hardness, in vitro protein adsorption, cytotoxicity, and 1 million cycles of accelerated aging wear test are completed; after passing the test, the product is aseptically vacuum packaged to obtain the finished shunt tube with silicone substrate for children.
[0064] Example 9 This embodiment verifies the effect of the lower limit of oxygen plasma activation time on the interfacial bonding strength of the coating.
[0065] This embodiment provides a ceramic-modified anti-sticking and anti-clogging ventriculoperitoneal shunt. The material, specifications and all subsequent processes of the medical flexible polymer substrate 5 are completely consistent with those of Embodiment 1. The only difference is that the oxygen plasma activation time in the substrate pretreatment is set to 5 minutes.
[0066] Example 10 This embodiment verifies the effect of the upper limit of oxygen plasma activation time on the interfacial bonding strength of the coating.
[0067] This embodiment provides a ceramic-modified anti-sticking and anti-clogging ventriculoperitoneal shunt. The material, specifications and all subsequent processes of the medical flexible polymer substrate 5 are completely consistent with those of Embodiment 1. The only difference is that the oxygen plasma activation time in the substrate pretreatment is set to 15 minutes.
[0068] Example 11 This embodiment verifies the effect of the upper limit of the auxiliary anode bias voltage inside the tube on the coating coverage effect of the silicone substrate tube during vacuum magnetron sputtering.
[0069] This embodiment provides a ceramic-modified, non-stick, and anti-clogging ventriculoperitoneal shunt tube, in which the auxiliary anode bias voltage inside the tube is set to -80V during sputtering. The material, specifications, and all subsequent processes of the medical flexible polymer substrate 5 are completely consistent with those of Embodiment 5.
[0070] Example 12 This embodiment verifies the effect of the lower limit of the auxiliary anode bias voltage inside the tube on the coating coverage effect of the silicone substrate tube during vacuum magnetron sputtering.
[0071] This embodiment provides a ceramic-modified, non-stick, and anti-clogging ventriculoperitoneal shunt tube, in which the auxiliary anode bias voltage inside the tube is set to -150V during sputtering. The material, specifications, and all subsequent processes of the medical flexible polymer substrate 5 are completely consistent with those of Embodiment 5.
[0072] Comparative Example 1 This comparative example provides a surface-modified ventriculoperitoneal shunt. The material and specifications of the medical flexible polymer substrate 5 of the shunt are completely consistent with those of Example 1. The surface coating is a pure titanium dioxide ceramic coating, which does not contain hydroxyapatite components, and the coating thickness is 650 nm.
[0073] The preparation process steps and parameters of this comparative example, including substrate pretreatment, precursor deposition, gradient curing, passivation polishing, testing and packaging, are exactly the same as those in Example 1.
[0074] Comparative Example 2 The same medical implantable polyurethane shunt tube substrate as in Example 1 was used, without ceramic precursor sol deposition modification treatment; the same degreasing and cleaning, oxygen plasma activation, low temperature gradient air-firing curing, surface polishing and passivation, and aseptic rinsing procedures as in Example 1 were performed to eliminate the performance influence caused by the substrate pretreatment and heat treatment process itself, and served as a blank baseline sample.
[0075] Comparative Example 3 The comparative example provides a surface-modified ventriculoperitoneal shunt, which differs from Example 1 only in that the mass ratio of titanium dioxide to hydroxyapatite in the composite bioceramic coating 6 is 1:1.5, which exceeds the 1:(0.8-1.2) ratio limit of the present invention, and the coating thickness is 650nm.
[0076] The parameters, preparation process, and operating conditions of the other medical flexible polymer substrates in this comparative example are completely consistent with those in Example 1.
[0077] Comparative Example 4 This comparative example provides a surface-modified ventriculoperitoneal shunt, which differs from Example 1 only in that: the thickness of the composite bioceramic coating 6 is 1000 nm, exceeding the coating thickness limit of 500-800 nm of this invention, and the mass ratio of titanium dioxide to hydroxyapatite is 1:1.
[0078] The parameters, preparation process, and operating conditions of the other medical flexible polymer substrates in this comparative example are completely consistent with those in Example 1.
[0079] Comparative Example 5 This comparative example provides a surface-modified ventriculoperitoneal shunt, which differs from Example 1 only in that the mass ratio of titanium dioxide to hydroxyapatite in the composite bioceramic coating 6 is 1:0.5, and the coating thickness is 650 nm.
[0080] The parameters, preparation process, and operating conditions of the other medical flexible polymer substrates in this comparative example are completely consistent with those in Example 1.
[0081] [Exemplary Animal Implantation Validation Protocol] To further evaluate the effectiveness and biocompatibility of the product in a living physiological environment, this invention also designed an in vivo implantation verification scheme, which is the verification test to be carried out in the future. The effectiveness of this invention mainly relies on various in vitro test data.
[0082] A piglet model of communicating hydrocephalus (3-4 weeks old, weighing 8-10 kg) was established using the kaolin pillow injection method. A total of 12 animals were randomly divided into two groups of 6 each. The experimental group was to be implanted with a ceramic-modified polyurethane shunt tube (full-surface TiO2-HA composite coating, TiO2:HA mass ratio of 1:1, coating thickness 650 nm) prepared in Example 1 of this invention. The control group was to be implanted with a blank polyurethane shunt tube, identical in material and specifications to the medical flexible polymer substrate 5 used in the experimental group, but without surface modification treatment, i.e., the tube described in Comparative Example 2.
[0083] After the ventriculoperitoneal shunt implantation surgery, the animals were routinely fed and observed. At the end of the predetermined observation period, the experimental animals were euthanized, and the shunt tube sample and surrounding target tissue were removed for evaluation according to the following testing methods: (1) Observation of coating integrity: The recovered diverter tube is cut open along the axial direction, dried at the critical point and then sprayed with gold. The surface condition of the coating is observed using a scanning electron microscope (SEM) to observe whether there is peeling, cracks or particle detachment. The magnification is 5000× and 20000×.
[0084] (2) Quantitative detection of protein deposition: A 1 cm length of sample from the recovery split tube was placed in PBS buffer containing 1% sodium dodecyl sulfate (SDS) and sonicated for 30 min to adsorb proteins on the surface of the desorption tube. The total amount of protein in the desorption solution was determined by the BCA protein quantification method and divided by the sample surface area to calculate the protein deposition per unit area (μg / cm²). Three parallel samples were set up for each group, and the test results were taken as the arithmetic mean.
[0085] (3) Histopathological examination: Periventricular brain tissue, greater omentum in contact with the shunt tube in the abdominal cavity, and abdominal wall soft tissue were collected, fixed in 10% neutral formalin, embedded in paraffin, and sectioned to a thickness of 5 μm for hematoxylin-eosin (HE) staining. The local inflammatory cell infiltration, degree of fibrosis, and thickness of the fibrous capsule were semi-quantitatively evaluated according to GB / T16886.6 / ISO10993-6 standards; grading criteria: Grade 0 - no reaction; Grade 1 - slight reaction; Grade 2 - moderate reaction; Grade 3 - severe reaction.
[0086] (4) General observation of the degree of adhesion: After the animal is euthanized, the abdominal cavity is opened and the adhesion between the abdominal segment 3 shunt and the greater omentum, mesentery and abdominal wall soft tissue is observed by the naked eye. The adhesion grading standards are as follows: Grade 0 - no adhesion, the shunt can move freely; Grade 1 - mild adhesion, can be easily separated by blunt dissection; Grade 2 - moderate adhesion, requires sharp dissection; Grade 3 - severe adhesion, the tissue is densely wrapped and difficult to separate.
[0087] The above-mentioned animal testing protocol allows for a comprehensive evaluation of the coating stability, protein deposition behavior, tissue adhesion level, and local tissue biocompatibility of the shunt tube under in vivo conditions, further demonstrating the practical application value of the technical solution of this invention.
[0088] The following method is used to test the anti-sticking and anti-clogging ventriculoperitoneal shunt tube on the ceramic surface in this invention: (1) Protein desorption rate test The shunt tubes prepared in each embodiment and comparative example were cut into standard samples of 2 cm length. At least three parallel samples were prepared for each group of samples, and the arithmetic mean of the test results was taken. Both ends and non-test surfaces of the samples were effectively sealed (e.g., using inert sealant or clamps), exposing only the coating surface. All samples were placed in a simulated cerebrospinal fluid flow loop at 37°C, pH 7.4, and containing 4.5 g / L bovine serum albumin (BSA), with a fluid rinsing flow rate of 5 mL / min, and continuous dynamic rinsing was performed. Samples were collected at 1 h, 3 h, 6 h, 12 h, and 24 h of rinsing, and the amount of residual protein adsorbed on the sample surface was determined using the BCA protein quantification method.
[0089] Using the baseline adsorption amount of the sample after immersion in static BSA solution at a constant temperature for 1 hour as the initial adsorbed protein amount, the protein desorption rate was calculated according to the following formula: Protein desorption rate (%) = (Initial adsorbed protein amount - Residual protein amount after flushing) / Initial adsorbed protein amount × 100%
[0090] (2) Coating adhesion test Referring to GB / T30707-2014 "Test Method for Adhesion of Fine Ceramic Coatings - Scratch Method", a diamond indenter was used to perform linear loading scratch tests on the coating surface at a loading rate of 10-100 N / min and a scratch length of 5-10 mm. During the test, the flexible sample was flattened and fixed on a rigid support plate to ensure that the sample did not slip relative to the surface during the scratching process. The critical load (Lc) at which the coating begins to crack or peel was determined by comprehensively analyzing the acoustic emission signal, friction-load curve, and scratch morphology (optical / SEM observation). At least three scratches were tested on each group of samples, and the arithmetic mean was taken. The higher the critical load value, the stronger the adhesion. To facilitate intuitive evaluation, this application also provides an adhesion rating standard of 1-5 based on the critical load Lc value range: Level 5 is the best (Lc≥35N), Level 4 (25N≤Lc<35N), Level 3 (15N≤Lc<25N), Level 2 (5N≤Lc<15N), Level 1 (Lc<5N), and Level 0 (complete peeling or no effective Lc value can be measured).
[0091] (3) Vickers hardness test of coating The hardness of the coating surface of each sample was tested using a nanoindenter. The indentation depth was strictly controlled within 1 / 10 of the coating thickness (i.e., indentation depth ≤ 50 nm) to avoid the 5-effect of the medical flexible polymer substrate. Each group of samples was tested 5 times and the average value was taken to record the true Vickers hardness of the coating surface.
[0092] (4) Accelerated aging and wear test All samples were placed in simulated cerebrospinal fluid (containing physiological inorganic salts and BSA protein components) at pH 7.4, under constant temperature and with weak circulation to simulate the dynamic environment of cerebrospinal fluid in vivo, and immersed for 7 days. Simultaneously, cyclic bending fatigue testing was conducted at a frequency of 1 Hz and a bending angle of 30°, accumulating 1 million cycles of bending to simulate long-term flexion and extension and fluid immersion after implantation in the human body. After the aging test, the protein desorption rate test and coating adhesion test were repeated to evaluate the performance retention ability of the samples under simulated conditions after long-term use.
[0093] The anti-protein adhesion ability, coating interfacial bonding strength, local hardness enhancement effect, and long-term implantation stability were tested according to the protein desorption rate test method, coating adhesion test method, coating Vickers hardness test method, and accelerated aging wear test method, respectively. The results are shown in Tables 1 and 2.
[0094] Table 1 Comparison of protein desorption rate, hardness ratio, adhesion and post-aging performance after 24 hours
[0095] Table 2 Comparison of protein desorption rates under different rinsing times
[0096] Under simulated cerebrospinal fluid shear scouring conditions, the dynamic desorption rate of the test samples (Examples 1-8) in the experimental group showed a steady upward trend with the extension of scouring time: 62.7% ± 0.6% at 1 h, 88.2% ± 0.7% at 6 h, and as high as 96.5% ± 0.5% at 24 h; while the desorption rate of the control group (uncoated blank control) was extremely low throughout the process, only 22.4% at 24 h. The desorption rate of the experimental group at 24 h was about 74.1 percentage points higher than that of the control group. This result indicates that the composite ceramic coating of the present invention, with its low surface energy and ultra-smooth surface characteristics, can achieve continuous dynamic self-cleaning under the action of fluid shear force, promote the desorption of adsorbed proteins on the surface, reduce protein accumulation on the pipeline surface, and help alleviate the risk of pipe blockage induced by protein accumulation. The test results of Examples 1-5 for adults and Examples 6-8 for children with small diameter pipes were all in a stable range, indicating that within the parameter range of the present invention, the prepared diverter pipe has stable performance regardless of whether it is a standard adult pipe or a small diameter child pipe.
[0097] In all embodiments, the Vickers hardness ratio remained stable between 4.00 and 4.50, which enhanced the resistance to extrusion and collapse deformation of the shunt port and the drainage side hole 4. The critical load Lc of the scratch test in all embodiments reached over 25N (corresponding to an adhesion rating of 4-5). After accelerated aging, the critical load retention rate was over 90% (Lc remained above 24N, with no or only a 1-level decrease in rating), proving that the coating and the medical polymer substrate 5 had a strong interfacial bond, and the coating could maintain its integrity under simulated stress conditions.
[0098] After 7 days of simulated cerebrospinal fluid immersion and 1 million cycles of accelerated aging bending, the protein desorption rate of each example remained above 98% after 24 hours, and the adhesion did not decrease significantly compared to before aging. This indicates that the coating did not undergo hydrolytic degradation or interface failure under long-term body fluid erosion and alternating stress, and possesses the durability required for lifelong implantation. Among them, Example 1 showed the best overall performance and represents the optimal implementation parameters; Example 5, using a silicone substrate and magnetron sputtering process, also performed excellently, proving that the present invention has broad applicability to different medical flexible polymer substrate materials.
[0099] Examples 6-8 are pediatric small-diameter shunt tube samples, respectively covered with polyurethane and silicone substrates. The tests showed that the hardness ratio was maintained at 4.10-4.40 times, and the critical load Lc was above 27N (adhesion level 4-5). After accelerated aging, the protein desorption rate was maintained at more than 98%, and the Lc retention rate was greater than 92%, proving that the process of the present invention is suitable for pediatric small-diameter ventriculoperitoneal shunt tubes and also has the comprehensive performance of low protein adsorption, dynamic self-cleaning and local anti-compression.
[0100] Examples 9 and 10 verified the lower limit of plasma activation time (5 min) and the upper limit of plasma activation time (15 min), respectively. The critical loads Lc reached 28.5 N and 40.5 N, respectively, with adhesion ratings of 4 and 5, respectively. The desorption rates after 24 h were 95.8% and 96.9%, respectively, and the performance remained good after accelerated aging. The above results indicate that excellent interfacial bonding and antifouling performance can be achieved within the entire range of 5-15 min of plasma activation time. Activation time shorter than 5 min results in insufficient grafting density of interfacial active groups and decreased bonding strength; activation time longer than 15 min may lead to peroxidation and embrittlement of the surface of the medical flexible polymer substrate 5. Therefore, the present invention limits the plasma activation time to 5-15 min based on clear critical criteria.
[0101] Examples 11 and 12 verified the lower limit of the magnetron sputtering bias voltage (-150V) and the upper limit (-80V), respectively. The critical loads Lc reached 34.8N and 41.2N, respectively, with adhesion ratings of level 4 and level 5, and 24-hour desorption rates of 96.0% and 96.5%, respectively. SEM observation showed that the coating on the inner wall of the cavity and the drainage side hole 4 was uniform and dense. The above results indicate that the bias voltage within the range of -150V to -80V can effectively guide plasma into the depths of the slender cavity, achieving uniform coating across the entire surface. When the absolute value of the bias voltage is below -80V, the plasma energy is insufficient to overcome the electric field shielding effect deep within the cavity, resulting in incomplete coating coverage at the far end and on the inner wall of the narrow drainage side hole 4. When the absolute value of the bias voltage is above -150V, excessive bombardment by high-energy ions may cause microcracks on the surface of the silicone substrate and a surge in internal stress in the coating. Therefore, this invention limits the auxiliary anode bias voltage inside the tube to -150V to -80V, which has clear critical control significance.
[0102] The 24-hour desorption rate of Comparative Example 1 was only 68.3%, decreasing to 52.1% after aging, indicating that the combination of titanium dioxide and hydroxyapatite has a synergistic effect. Using titanium dioxide alone cannot meet the long-term anti-adhesion requirements under simulated conditions. Comparative Example 3 had a hardness ratio decreasing to 3.60, with a critical load Lc of only 12.6 N (adhesion grade 2), and its performance significantly deteriorated after aging. Comparative Example 4 had an Lc of only 8.2 N (adhesion grade 1), decreasing to grade 0 after aging, resulting in complete coating peeling. The 24-hour desorption rate of Comparative Example 5 was only 72.4%, with a critical load Lc of only 14.2 N (adhesion grade 2). The reasons for this are: insufficient hydroxyapatite content, lack of biocompatible components in the composite ceramic coating, imbalance in the surface energy regulation of the coating, and a significant decrease in dynamic self-cleaning ability; simultaneously, the imbalance in the two-phase composition ratio caused increased internal stress in the coating, leading to a decrease in the interfacial bonding strength between the coating and the polymer. The results demonstrate that when the proportion of hydroxyapatite is below the lower limit of the proportion specified in this invention, the antifouling performance and interfacial bonding performance of the coating will significantly deteriorate, failing to meet the requirements for long-term use in implantable medical devices. These results indicate that exceeding the proportion and thickness range specified in this invention will disrupt the uniformity of the coating's microstructure, leading to internal stress imbalance and decreased interfacial bonding, severely impairing the long-term reliability of the coating under implantation conditions.
[0103] In summary, the ceramic surface-modified anti-adhesion and anti-clogging ventriculoperitoneal shunt prepared by this invention has achieved excellent results in terms of anti-protein adhesion, dynamic self-cleaning, local hardness enhancement and simulated stability. It is beneficial to improve the performance defects corresponding to protein deposition clogging, tissue encapsulation clogging and port deformation clogging, and has good potential for medical device development.
Claims
1. A ceramic-surface-modified, anti-sticking, and anti-clogging ventriculoperitoneal shunt, characterized in that: The device includes a shunt tube substrate made of medical flexible polymer, the shunt tube being divided into a ventricular segment, a valve connection segment, and a peritoneal segment; the entire inner wall, outer wall, drainage side holes, and end ports of the ventricular and peritoneal segments are covered with a dense titanium dioxide-hydroxyapatite composite bioceramic coating; the mass ratio of titanium dioxide to hydroxyapatite is 1:(0.8-1.2); the composite bioceramic coating has a thickness of 500-800 nm and a surface roughness of 0.03-0.05 μm; the composite bioceramic coating is a drug-free coating, and the coating is dense, non-porous, and free of easily detached particles.
2. The ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt tube according to claim 1, characterized in that: The medical flexible polymer is polyurethane or medical silicone.
3. The ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt tube according to claim 1, characterized in that: The Vickers hardness of the composite bioceramic coating is 4-4.5 times that of the Vickers hardness of the medical flexible polymer substrate.
4. The ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt tube according to claim 1, characterized in that: The adhesion between the composite bioceramic coating and the medical flexible polymer substrate satisfies the following condition: critical load Lc≥25N.
5. The method for preparing the ceramic surface-modified anti-sticking and anti-clogging ventriculoperitoneal shunt according to any one of claims 1-4, characterized in that, Includes the following steps: 1) Substrate pretreatment: Degrease and clean the molded polymer manifold and activate it as a whole with oxygen plasma; 2) Ceramic precursor deposition: The deposition method is selected according to the substrate material of the manifold. The polyurethane substrate pipeline adopts the sol-gel negative pressure wetting method, and the silicone substrate pipeline adopts the vacuum magnetron sputtering method. Ceramic precursor films are deposited on the entire inner wall, outer wall, drainage side hole and both ends of the manifold. 3) Low-temperature gradient curing crystallization: The low-temperature gradient curing adopts a segmented heating method, with the highest curing temperature being lower than the heat distortion temperature of the corresponding medical flexible polymer substrate. Ceramic crystallization is completed through segmented heating, segmented heat preservation, and cooling at a rate of ≤0.5℃ / min. 4) Surface passivation and polishing: The surface of the shunt tube is polished with diamond micro powder with high precision and then passivated with medical passivation liquid to seal microscopic defects in the coating. 5) Testing and Packaging: The finished product undergoes coating adhesion, Vickers hardness, in vitro protein adsorption, cytotoxicity, and simulated cerebrospinal fluid immersion + cyclic bending accelerated aging and wear tests. After passing the performance tests, it is aseptically packaged.
6. The preparation method according to claim 5, characterized in that: The negative pressure condition of the sol-gel negative pressure impregnation method is -0.08MPa, and the negative pressure is maintained for 5-6 minutes to allow the ceramic sol to fully impregnate the entire inner wall, outer wall, drainage side hole and the surface of both ends of the diversion tube.
7. The preparation method according to claim 5, characterized in that: In the low-temperature gradient curing and crystallization process, adult standard polyurethane tubing adopts a segmented heat preservation program of 50℃ for 30 minutes, 65℃ for 40 minutes, and 80℃ for 20 minutes; silicone tubing and / or children's small diameter tubing adopts a segmented heat preservation program of 50℃ for 20 minutes, 62℃ for 30 minutes, and 75℃ for 15 minutes.
8. The preparation method according to claim 5, characterized in that: In the vacuum magnetron sputtering method, the cavity is evacuated to 1.0 × 10⁻⁶ m³ / s. -4 After a high vacuum of Pa, a trace amount of oxygen is introduced, and a dual-target co-sputtering of pure titanium and hydroxyapatite is used with a total power of 200W. Titanium dioxide and hydroxyapatite components are deposited simultaneously and their mass ratio is controlled to be 1:(0.8-1.2). During the sputtering process, the plasma is guided into the inner wall of the tube by an auxiliary anode bias voltage, which is controlled between -150V and -80V.
9. The preparation method according to claim 5, characterized in that: The oxygen plasma activation time in the substrate pretreatment is 5-15 minutes. The pretreatment waste liquid and activation tail gas are purified to be harmless. The residual sol waste liquid after the ceramic precursor deposition is recycled and reused in a closed system.
Citation Information
Patent Citations
Device capable of automatically adjusting shunt volume of cerebrospinal fluid and preventing shunt tube from being blocked
CN103800991A
Bacterium resisting anticoagulant ventriculoperitoneal branch pipe silicone pipe body and preparation method and application thereof
CN110694118A
Novel antibacterial antifouling coating material as well as preparation method and application thereof
CN117736618A